Equality Agenda, Sustainable Development Goals, and Muslim Countries’ Acceptance of LGBTQ - Tika Tazkya Nurdyawati; Anne Mardiah; Raden Radhitya Rizal (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2021)
The Sustainable Development Goals (SDGs) are an agenda designed by world leaders to reduce and protect the global world. The fifth of these goals is gender empowerment. Many narratives related to the rights of the LGBTQ (lesbian, gay, bisexual, transgender, queer) community have often emerged, and the community has even experienced threats in several Islamic countries that still adhere to sharia law. This article aims to examine how the SDGs can influence Muslim countries’ policies toward the acceptance of their domestic LGBTQ community. Using Samuel P.Huntington's Clash of Civilizations theory, this research employs Atlas.ti toqualitatively analyse data collected from many sources. This research finds that thefifth SDG cannot yet be fully incorporated into the policies of Muslim countries, i.e.,those that have implemented sharia law. The SDGs are part of a Western globalistagenda that failed to take into account the different cultures and beliefs held aroundthe world. Furthermore, the issues of cultural identity contained within the SDGs arefar more sensitive than these goals' economic components. It is this sensitivity thathas driven debate and conflict over the fifth SDG. The SDGs are ultimately unable tochange deep-rooted policies, especially those rooted in the ideologies of nationsthat forbid LGBTQ.